(untitled) (Asian Journal of Medical and Biological Research, 2020)
Today, in an era of antibiotic-resistant pathogens and other looming microbial threats, the value of prevention of infection is recognized. To circumvent the indiscriminate use of antibiotics and emerging resistance to them, to reduce the use of chemical preservatives and to abate abdominal, gastrointestinal and urogenital disorders- probiotics and bacteriocins are getting paramount priority in recent times. We investigated the probiotic and bacteriocinogenic potentiality of Lactobacillus isolated from milk products. 15 lactic acid bacteria (LAB) were isolated from milk product samples using De Man Rogosa Sharpe (MRS) medium. Among them, only one (6%) isolate showed potential antibacterial activity against Staphylococcus aureus, Escherichia coli, Salmonella typhi, Pseudomonas aeruginosa and Bacillus subtilis in agar well diffusion method. Following conventional methods, genus and species of the isolate were confirmed as Lactobacillus xylosus. The isolate exhibited growth competency at wide range of temperatures (27-45°C), pH (2-9), NaCl (1-7%), bile salt (0.5-2%) and could produce bacteriocin or BLS, thus implying its potential probiotic nature. Bacteriocins or BLS produced by Lactobacillus xylosus inhibited E. coli and S. aureus and could retain their antibacterial activity at wide range of temperatures (37°C to 100°C) and pH (2–9) treatments. These crude bacteriocins or BLS of 5% concentration reduced the initial bacterial load of cheese and milk up to 41% and 43% respectively, after 48 h of preservation at room temperature. The experimental data revealed that our study isolate Lactobacillus xylosus could be used as probiotics and their bacteriocin or BLS could be used as bio-preservatives. Asian J. Med. Biol. Res. March 2020, 6(1): 27-37